Investigasi Numerik Perkerasan Jalan Sistem Pelat Terpaku terhadap Variasi Dimensi Struktur - Puri, Anas; Mildawati, Roza (BENTANG : Jurnal Teoritis dan Terapan Bidang Rekayasa Sipil, 2019)
An innovation in rigid pavement engineering was developed by using Nailed-slab Pavement System. In this case, the rigid pavement is reinforced by short micro piles underneath to increase the performance of pavement on soft subgrade. In this paper%2